Происхождение удмуртского народа: [монография] / М. Г. Атаманов-Эграпи - Атаманов-Эграпи Михаил Гаврилович (Удмуртия, 2010)
Экземпляры: ХР (20161128) / Инвентарный номер: 43076 / Цена: 179.89 / Авт.знак: А 92 / ГРНТИ: 03 / ББК: 63.521(=664)